2018
DOI: 10.1108/rpj-03-2017-0045
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the 3D-printing technology on the physical and mechanical properties of polyphenylene sulfone

Abstract: Purpose This paper aims to examine the impact of three-dimensional (3D) printing technological modes (using fused deposition modelling [FDM]) on physical and mechanical properties of samples from polyphenylenesulfone. Design/methodology/approach For this study, the standard test samples were printed using the FDM method at different filament orientation angles, the gaps between them and a different width. The basic physical and mechanical properties, such as the strength, the elastic modulus and the impact st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…Vishwas et al (2018) observed that orientation and shell thickness were the highest significant process parameters for mechanical properties of ABS and nylon parts. Slonov et al (2018) performed experiments to find the influence of factors on the mechanical properties of polyphenylenesulfone. Elastic modulus varies as the air gap changes, and it is independent of the raster angle.…”
Section: Fused Deposition Modelling Part Quality and Performance Improvementmentioning
confidence: 99%
“…Vishwas et al (2018) observed that orientation and shell thickness were the highest significant process parameters for mechanical properties of ABS and nylon parts. Slonov et al (2018) performed experiments to find the influence of factors on the mechanical properties of polyphenylenesulfone. Elastic modulus varies as the air gap changes, and it is independent of the raster angle.…”
Section: Fused Deposition Modelling Part Quality and Performance Improvementmentioning
confidence: 99%
“…3(a)). Concurrently, Khashirova and co‐workers 10 investigated the relationship between FFF printing angle and mechanical properties. They found that interlayer adhesion imparted from altered printing angles directly relates to material properties (Fig.…”
Section: Am Of Polysulfonesmentioning
confidence: 99%
“…Sulfone‐based polymer microscopy: (a) FFF of poly(phenylene sulfone) 9 ; (b) FFF of poly(phenylene sulfone) with pitched printing 10 ; (c) Lattice printed with 40 wt% PSU using DIW printer 11 ; (d) 80 μm PSU particles for SLS 12 …”
Section: Am Of Polysulfonesmentioning
confidence: 99%
“…In FFF processing, the build orientation is defined as the nozzle direction applied in the 3D printer when it is operated to deposit layers of material to build up the printed parts [29,30]. There are three types of build orientation in FFF process, i.e.,…”
Section: Adjustments Of the Printing Parameters Used In Fffmentioning
confidence: 99%